NEUROGENE-GENETIC FACTORS AND MECHANISMS DEVELOPMENT OF ULCER DISEASE - Леонид Николаевич Иванов; Марина Леонидовна Колотилова (Медицина в Кузбассе, 2020)
Purpose of the study – to develop an improved author's theory of the etiology of the pathogenesis of peptic ulcer.